Strategies coping climate change: a study of companies listed on the Corporate Sustainability Index B3 - Cruz, Thayse Santos; Gomes, Sonia Maria Silva; Oliveira, Nverson Cruz; Oliveira, Neylane Santos (Revista de Administração da UFSM, 2017)
This research investigated strategies coping climate change evidenced by the companies listed in the Corporate Sustainability Index (ISE) of B3, in the period from 2011 to 2014. Therefore, there was content analysis of the answers provided in the dimension climate change questionnaire ISE. Based on the results, there is a growing trend of companies that have their corporate policy on climate change approved by senior management, which establishes GHG emission reduction targets and to assume public commitments on GHG reduction targets. In addition to using internationally accepted parameters, a significant portion of organizations submit their GHG inventories to check an independent third party. In terms of disclosure, most companies participated in the Carbon Disclosure Project. The findings indicate that companies are entering in their management models different strategies, which seek to create value for stakeholders. These results are in line with the theory of stakeholders. Through this research, there have been indications of the level of proactivity organizational in relation to the challenge of climate change. Through these results, contributes up to expand discussions on climate issues and their implications for corporate strategies for achieving sustainability.